Survival strategies and family roles in micro-family food businesses during covid-19 pandemic in selangor - Abdul Majid, Mohd Aliff; Tamby Chik, Chamah; Arsat, Aliffaizi; Azman, Ana Batrisyia (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
Micro-, small, and medium-sized businesses (MSMEs), especially micro-family food businesses (MFFBs), are essential to Malaysia's economy. The COVID-19 pandemic has, however, posed significant challenges for these businesses, particularly in the Klang Valley. This study explores the unique struggles faced by MFFBs and the innovative strategies they employed to survive and thrive during the crisis, emphasizing the role of family dynamics in shaping these strategies. Using a qualitative approach, the research includes semi-structured interviews with six MFFB owners, selected through purposive sampling. Thematic analysis of the data revealed 15 key themes. The first four themes highlight the challenges of revenue loss, financial instability, potential closures, and employee-related issues. The next seven themes focus on the strategies MFFBs implemented, including benevolence, commitment to food quality, adaptability, takeaway management, strategic planning, menu diversification, and technology integration. Additionally, four themes—reliance, task division, deference, and responsibility—underscore the influential role of family members in decision-making. The study reveals that the family unit is not only a support system but also a driving force behind innovation and strategic responses. These findings enhance the understanding of how MFFBs, supported by strong family ties, demonstrate resilience and adaptability in navigating the challenges posed by the pandemic, offering insights into the critical role of familial involvement in MSME sustainability.